Design of the PF-ILD trial: a double-blind, randomised, placebo-controlled phase III trial of nintedanib in patients with progressive fibrosing interstitial lung disease. Issue 1 (17th September 2017) - Flaherty, Kevin R; Brown, Kevin K; Wells, Athol U; Clerisme-Beaty, Emmanuelle; Collard, Harold R; Cottin, Vincent; Devaraj, Anand; Inoue, Yoshikazu; Le Maulf, Florence; Richeldi, Luca; Schmidt, Hendrik; Walsh, Simon; et al.
Abstract : 600 patients aged ≥18 years will be randomised in a 1:1 ratio to nintedanib or placebo. Patients with diagnosis of IPF will be excluded. The study population will be enriched with two-thirds having a usual interstitial pneumonia-like pattern on HRCT. The primary endpoint is the annual rate of decline in forced vital capacity over 52 weeks. The main secondary endpoints are the absolute change from baseline in King's Brief Interstitial Lung Disease Questionnaire total score, time to first acute interstitial lung disease exacerbation or death and time to all-cause mortality over 52 weeks. Ethics and dissemination: The trial is conducted in accordance with the Declaration of Helsinki, the International Conference on Harmonisation Tripartite Guideline for Good Clinical Practice (GCP) and Japanese GCP regulations. Trial registration number: NCT02999178.